Strategi Manajemen Berbasis Tagline Dalam Memperkuat Kerja Sama International : Program Penguatan Citra Globab Universiti Malaysia Perlis ( UNIMAP). - Arifah, Rena; Alam, Hermansyah; Parinduri, Luthfi; Harahap, Raja; Hasibuan, Abdurrozaq (Cattleya Darmaya Fortuna, 2025)
In this era of globalization, international collaboration in higher education has become a key factor in improving academic quality, research, and technological development. Universiti Malaysia Perlis (UniMAP), as an institution that focuses on technical and vocational education, utilizes the philosophy encapsulated in its tagline: